Analisis Kesantunan Berbahasa dalam Film Ancika 1995 Karya Pidi Baiq - Nopita Sari; Henny Nopriani; Ike Tri Pebrianti (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Baturaja, 2025)
The purpose of this study is to describe the form of politeness in the film Ancika 1995 by Pidi Baiq. This type of research is qualitative research. The subject of this study is the form of speech or conversation in the dialogue of the film Acika 1995 by Pidi Baiq. Data collection techniques are in the form of listening techniques and note-taking techniques. The data analysis technique in this study uses the work analysis technique. The results of this research concluded that in compliance with the principles of politeness in language through the dialogue or conversations of the characters in the film Ancika 1995, six principles of politeness in language were found to be adhered to, which were divided into compliance with the principle of wisdom in 6 utterances, compliance with the principle of generosity in 7 utterances, compliance with the principle of praise in 10 utterances, adherence to the principle of humility in 4 utterances, adherence to the principle of consensus in 14 utterances and Compliance with the principle of sympathy. a total of 7 utterances, a total of 47 utterances complying with the principles of language politeness.